Audit as a tool for enhancing the reliability of financial statements: a case study of Farafenni General Hospital, The Gambia, West Africa - Fatty, Muhammed; Rahman, Arief (Proceeding International Conference on Accounting and Finance, 2026)
Main Objective – This research aims to examine the role of auditing as a tool for enhancing the reliability of financial statements, focusing on Farafenni General Hospital in The Gambia, West Africa. The study explores how auditing contributes to accountability, transparency, and stakeholder confidence within a public health institution, while also identifying the institutional challenges that limit its effectiveness. Design/Methodology/Approach – The research adopts a qualitative design using a case study approach. Data were collected through semi-structured interviews with senior management, finance staff, external auditors, and oversight bodies. The analysis was conducted using NVivo 15 software, guided by Agency Theory, to uncover patterns of accountability, communication, and audit effectiveness. Key Findings – The findings reveal that auditing performs corrective, preventive, and assurance functions that collectively strengthen financial reporting reliability. External audits promote accountability and donor confidence by providing independent verification of financial information. However, the absence of an internal audit unit, weak communication channels, and delayed implementation of audit recommendations undermine the overall impact of auditing. These weaknesses create recurring reporting issues and limit the hospital’s ability to maintain continuous financial reliability. Theoretical and Practical Implications – The study reinforces the relevance of Agency Theory in explaining the relationship between auditors, management, and oversight bodies. It highlights that while audits reduce information asymmetry, institutional and political constraints can weaken their monitoring function. Practically, the study recommends establishing an internal audit unit, digitizing financial records, and strengthening feedback mechanisms between auditors and management to improve financial governance and accountability in public hospitals. Novelty – This research is the first to provide an in-depth qualitative analysis of how auditing enhances financial reliability within a Gambian public hospital context. By integrating the perspectives of auditors, management, and oversight institutions, the study contributes original insights into the structural, behavioral, and governance factors shaping audit effectiveness in the public health sector of The Gambia, West Africa.